The meanings of the term gender in modern Western studies - Alalak, Ahmed (Al-Adab Journal, 2024)
The term gender is one of the terms that has sparked widespread controversy in Iraq in the recent period. The researcher worked on reviewing a group of recent research and studies for the year (2023). Is gender an alternative term to sex, or does it mean social sex, or does it have another meaning? The study aimed to find out what it means. Gender through modern studies in psychology, and has there been a change in the concept of the term? When defining the terms, the researcher dealt with two definitions of the American Psychological Association, which show that there is a relative difference in the concept. After the association was defined it as the attitudes, feelings, and behaviors that a certain culture associates with the biological sex of a person in the year ( (2010) changed to mean gender identity and gender expression. The study also reviewed (27) authors and studies by searching for the term in English in Google Scholar and selecting the first results. The researcher concluded that modern studies are divided into two parts, the first deals with gender. As an alternative concept to gender, which divides it into males and females, these studies aim for equality. As for the second part of the studies, it dealt with sexual deviants and presented them as natural (social types) and tried to treat the psychological disorders they suffer from, which they attributed to what it calls minority oppression. The researcher recommended the necessity of emphasizing the use of the term Sex, because this will close the door to sexual deviations that are intended to be legitimized scientifically and legally. The researcher also suggested conducting a study on the term gender as it is understood by psychologists in Iraq.